Neural network based receivers for communication systems - Sowmya Sundararajan. (2009)
Continuous phase modulation (CPM) schemes are attractive for use in peak-power limited transmission systems such as satellite transmission systems. However, their drawback lies in their prohibitively complex receiver structures. They consist of a bank of matched filters followed by a Viterbi decoder which draws heavily on computational resources. Feed-forward neural-nets are therefore proposed to replace this complex receiver structure.